Contested issues in student affairs : diverse perspectives and respectful dialogue - Magolda, Peter Mark; Baxter Magolda, Marcia B., 1956- (Stylus Publishing, 2011)
Contested Issues in Student Affairs augments traditional introductory handbooks that focus on functional areas (e.g., residence life, career services) and organizational issues. It fills a void by addressing the social, educational and moral concepts and concerns of student affairs work that transcend content areas and administrative units, such as the tensions between theory and practice, academic affairs and student affairs, risk taking and failure; and such as issues of race, ethnicity, sexual orientation, and spirituality.